The Role of Cotton Production in the Textile Supply Chain and the Study of the Amount of Pollution Production: A System Dynamic Study - Faezi, Zahra; Alikhademi, Azam (American Journal of Social Sciences and Humanities, 2021)
Textile industry uses massive amounts of cotton annually and as the population of the world grows, the more people need textile, and the more cotton needs to be harvested. This study was an attempt to examine the impact of cotton production of the textile supply chain on people and the ecosystem. The data has been gathered from FAO, WHO, and other valid databases. Thirty participants were also asked to answer a questionnaire, who were proficient farmers acquainted with cotton cultivation. The questions were analyzed by System Dynamics (SD) Model to explore water, air and soil pollution, mortality and poisoning of humans and animals, and the use of pesticides. The findings of this study revealed that cotton production not only does have significant but also increasing repercussions for the environment and humans. These effects are especially worrying when 40% of this cotton is used in the enormous and ever-increasing textile industry, hence, in the end, suggestions have made on cutting down on them.